A Modest Proposal for Peace among People of Peace - Wenger, Jay L. (Advances in Social Sciences Research Journal, 2016)
People in the United States are passionate about a variety of political issues, causing conflicts far too often. In this essay, five steps are identified for reducing the effects of such conflicts, thus improving the chances for peace/harmony among people who disagree. Supportive research is described. Mennonites are people of religious faith. They are also considered to be people of peace. The five steps are described within the context of the conflicts Mennonites are currently experiencing regarding same-sex marriages. The five steps, however, should be applicable to any situation in which people are dealing with very different opinions about very important issues.